Neonatal somatic oxygenation and perfusion assessment using near-infrared spectroscopy - Kooi, Elisabeth M. W.; Mintzer, Jonathan P.; Rhee, Christopher J.; Ergenekon, Ebru; Schwarz, Christoph; Pichler, Gerhard; de Boode, Willem P. (Pediatric research, 2024)
In this narrative review, we summarize the current knowledge and applications of somatic near-infrared spectroscopy (NIRS), with a focus on intestinal, renal, limb, and multi-site applications in neonates. Assessing somatic oxygenation at various body locations in neonates may aid in the understanding of underlying pathophysiology of organ injury. Considering cerebral autoregulation may be active to protect the brain during systemic circulatory failure, peripheral somatic oxygenation may potentially provide an early indication of neonatal cardiovascular failure and ultimate hypoxemic injury to vital organs including the brain. Certain intestinal oxygenation patterns appear to be associated with the onset and course of necrotizing enterocolitis, whereas impaired renal oxygenation may indicate the onset of acute kidney injury after various types of hypoxic events. Peripheral muscle oxygenation measured at a limb may be particularly effective in the early prediction of shock in neonates. Using multi-site NIRS may complement current approaches and clinical investigations to alert for neonatal tissue hypoxemia, and potentially even guide management. However, somatic NIRS has its inherent limitations in regard to accuracy. Interpretation of organ-specific values can also be challenging. Last, currently there are limited prospective intervention studies, and clinical benefits need to be examined further, after the clarification of critical threshold-values.
Gesehen am 25.11.2024